2007
DOI: 10.1525/sp.2007.54.4.523
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Same-Sex Attraction and Academic Outcomes: The Role of School Attachment and Engagement

Abstract: Schools create environments in which some sexual feelings, behaviors, and relationships are stigmatized, and this may have negative consequences for adolescents with nonheterosexual romantic attractions. This stigma can lead them to withdraw and disengage from school at a critical time of preparation for adulthood, which can compromise opportunities for future success. Previous research has demonstrated that sexual minority youth report greater levels of school-related problems, including a weaker sense of att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
105
4
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(119 citation statements)
references
References 46 publications
5
105
4
2
Order By: Relevance
“…Overall, sexual minority participants' GPA was higher than that of the non-minority. This finding was inconsistent with previous studies abroad which suggested the opposite (Pearson, Muller & Wilkinson, 2007;Rostosky, Owens, Zimmerman & Riggle, 2003). This may possibly be explained by findings from the qualitative phase, where some of the sexual minority participants regarded they had to study hard and do better in order to compensate for their sexuality and not be disrespected.…”
Section: Discussioncontrasting
confidence: 88%
“…Overall, sexual minority participants' GPA was higher than that of the non-minority. This finding was inconsistent with previous studies abroad which suggested the opposite (Pearson, Muller & Wilkinson, 2007;Rostosky, Owens, Zimmerman & Riggle, 2003). This may possibly be explained by findings from the qualitative phase, where some of the sexual minority participants regarded they had to study hard and do better in order to compensate for their sexuality and not be disrespected.…”
Section: Discussioncontrasting
confidence: 88%
“…Moreover, previous studies pointed out that school engagement improves academic achievement, higher school completion rates, and increases student sense of connecting in schools and other social institutions (Finn, 1989;Marks, 2000;Pearson, Muller, & Wilkinson, 2007;Willms, 2003). Higher school engagement has been linked with high school graduation and academic success (Furrer & Skinner, 2003).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Since many youth go through adolescence and the associated developmental tasks while in high school, such settings are a key place of socialization and exposure to ecological factors that may affect the development of LGBTQ youth (Pearson, Muller, & Wilkinson, 2007).…”
Section: High School Settings For Lgbtq Youthmentioning
confidence: 99%
“…Some evidence suggests that the school climate may be particularly difficult for transgender and gender non-conforming youth, with greater likelihood of experiencing assault, harassment, feeling unsafe, and missing days of school due to fear compared to LGB youth (Kosciw, Greytak, Bartkiewicz, Boesen, & Palmer, 2012;Kosciw, Greytak, Bartkiewicz, Boesen, & Palmer, 2014). Such risks within the school climate can deeply impact the interaction between individual students and the school setting, producing difficulties for LGBTQ youth that extend into adulthood (Pearson et al, 2007).…”
Section: High School Settings For Lgbtq Youthmentioning
confidence: 99%